Bhāratanī eka virala vibhūti Śrī Dhīrajalāla Śāha - Tripāṭhī, Rudradeva, 1925- (Śatāvadhānī Paṇḍita Śrī Dhīrajalāla Ṭokaraśī Śāha Amrtamahotsava Samiti, 1981)
Biography of Dhirajlal Tokershi Shah, b. 1906, Jain religious leader and Gujarati litterateur.